Pulmonary functions in sewage workers - Karande, Shilpa P.; deSouza, Roemarie; Asagaonkar, Dileep; Dhokar, Sudhir; Pose, Meghna; I., Vasanthi (International Journal of Research in Medical Sciences, 2022)
Background: Occupational lung diseases in sewage workers have not received sufficient attention, despite chronic exposure to noxious material. We aimed to describe the pulmonary function testing pattern of sewage workers with special emphasis on estimated lung age. Methods: We included sewage workers who came for health check-up. We excluded patients who had respiratory infection/any other respiratory ailments. Socio-demographic profile, history and examination were noted. Routine haematological investigations, chest radiograph, PFT were done. Basal and predicted measurements FVC, FEV1, PEFR, FE F25-75%, MVV and estimated lung age were noted. Results: Average age was 43.48±7.96 years on presentation and no one was symptomatic, everyone had normal X-ray chest findings. Of these 82 participants,36 had normal pattern on PFT. Out of 46 abnormal patterns, 28 had obstructive,5 restrictive and 13 had mixed patterns. In Obstructive pattern, mean FEV1/FVC ratio was 78.15 + 4.42 %, FEV1% was 89.26+10.27 %. In restrictive pattern, mean FVC % was 71%±5.72. In mixed pattern mean FVC % was 71.83+10.7%, FEV1 % was 70.98+6.43%.FEF (25-75%) was 62±10.85% in the obstructive pattern and 93±11.49% in the restrictive pattern. Estimated lung age was found to be 45±10.71 years, 55±11.36 years and 67±7.54 years in normal, obstructive and restrictive pattern which was high. Conclusions: There is a considerable burden of occupation lung diseases in the form of reduced lung functions among sewage workers, which often goes undiagnosed. Periodic assessment and appropriate measures in reducing the exposure should be considered.